Innovative positioning of the goalkeeper in defence of seven-meter penalty shots in handball - Rogulj, N.; Papic', V.; Foretic, N.; Srhoj, V.; Cavala, M. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
A goalkeeper must rely on precise positioning and setting. His basic aim is to take the most favourable position, with regard to the characteristics of the shot. This article suggested an innovative mathematical model to calculate the move and the rotation angle in the defence of seven-metre penalty shots which enables maximal body usage as a passive defensive area, the shortest way of body parts in performing defensive movements and equal availability of all the parts of the goal, which, in the end, may result in the higher efficiency in defending penalty shots.